Dielectric spectroscopy and electrical conductivity measurements on high-tilted antiferroelectric materials. (1st September 2020) - Nepal, Shantiram; Das, Banani; Das, Malay Kumar; Strójwąs, Katarzyna; Urbańska, Magdalena
ABSTRACT: Dielectric spectroscopic measurements have been reported on three synthesized pure liquid crystalline compounds having paraelectric (SmA*), ferroelectric (SmC*) and antiferroelectric (SmCA *) phases in the frequency range of 40 Hz–25 MHz. Several relaxation modes i.e. low-frequency PL Mode and high-frequency PH Mode in the SmCA * phase, Goldstone Mode (GM) in SmC* phase and Soft Mode (SM) in SmA* phase have been observed. These materials with wide antiferroelectric range are found to possess low relaxation times, thus making them promising materials for applications. The Cole–Cole plot shows the modes in the SmCA * phase to be much weaker than in the SmC* phase. Dielectric loss is maximum in SmC* phase due to the Goldstone Mode. Additionally, the AC electrical conductivity is found to be maximum in the SmC* phase and is dependent on the frequency. Maximum DC conductivity of these materials is of the order of 10 −5 Ohm −1 m −1 .